2001
DOI: 10.1016/s0022-4049(00)00169-9
|View full text |Cite
|
Sign up to set email alerts
|

Adding structure to MV-algebras

Abstract: We study the algebras corresponding to various extensions of Lukasiewicz infinite-valued logics. In particular, we study the structures resulting from adding the characteristic function for truth, adding an arithmetical product, and the corresponding residuation operator. We characterize the free algebras in the relative equational classes, and we discuss their spectral spaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Basically, the idea we follow to achieve the characterisation we are looking for is an extension of the technique used in [20], where, among others, the following result is proved.…”
Section: Definition 38mentioning
confidence: 99%
“…Basically, the idea we follow to achieve the characterisation we are looking for is an extension of the technique used in [20], where, among others, the following result is proved.…”
Section: Definition 38mentioning
confidence: 99%
“…These algebras are known as PMValgebras or PŁ-algebras (see [7] and [6]). Then we combine these two extensions and get algebras known as PMV 4 -algebras or PŁ 0 4 -algebras (see [8] and [6])…”
Section: Preliminariesmentioning
confidence: 99%
“…First of all, Mundici's equivalence between MV-algebras and lattice-ordered abelian groups with strong unit [Mu86] may be extended to a class of algebras which at the same time constitutes the algebraic semantics for an extension of Lukasiewicz Logic, and forms a category equivalent to a suitable category of lattice-ordered rings. This idea has been developed in [DND01], [M00], [EGM01], [M01] and [MP01]. The paper [DND01] treats products in a general setting, whereas the other papers describe a product which is closely related to the product in the reals.…”
Section: Introductionmentioning
confidence: 99%
“…Then ⊕, , · and / are the truncations to [0, 1] of the four basic operations, sum, subtraction, product and division. The papers [M00], [EGM01], [M01] and [MP01] contain a detailed treatment of LΠ-algebras. In particular, it is shown that these algebras constitute a discriminator variety, hence in every subdirectly irreducible LΠ-algebra universal properties can be expressed by means of identities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation